Duality and decay of macroscopic F-strings - Skliros, Dimitri P.; Copeland, Edmund J.; Saffin, Paul M. (American Physical Society, 2013)
We study the decay of fundamental string loops of arbitrary size L/min(n,m)≫√α′, labeled by (n, m; λn, ¯λm), where n, m correspond to left- and right-mover harmonics and λn, ¯λm to polarization tensors, and find that a description in terms of the recent coherent vertex operator construction of Hindmarsh and Skliros is computationally very efficient. We primarily show that the decay rates and mass shifts of vertex operators (n, m; λn, ¯λm) and their “duals” (n, m; λn, ¯λ∗m) are equal to leading order in the string coupling, implying, for instance, that decay rates of epicycloids equal those of hypocycloids. We then compute the power and decay rates associated with massless IR radiation for the trajectory (1, 1; λ1, ¯λ1), and find that it is precisely reproduced by the low energy effective theory of Dabholkar and Harvey. Guided by this correspondence, we conjecture the result for arbitrary trajectories (n, m; λn, ¯λm) and discover a curious relation between gravitational and axion plus dilaton radiation. It is now possible to start exploring string evolution in regimes where a low energy effective description is less useful, such as in the vicinity of cusps.